2014
DOI: 10.1111/tbj.12274
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Geographic Differences in Immediate Reconstruction after Mastectomy in the United States

Abstract: Disparities are evident in breast cancer diagnosis, treatment, and outcomes. This study examines multiple socioeconomic and geographic regions across the US to determine if disparities exist in the type of reconstruction obtained after mastectomy. This is a retrospective study evaluating socioeconomic and geographic variables of 14,764 women who underwent mastectomy in 2008 using the Nationwide Inpatient Sample (NIS). Statistical analysis was performed on three groups of women: patients without reconstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 34 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…21–24 A cross-sectional study of women with early stage breast cancer identified factors affecting BCT versus mastectomy choice and found that age >70 years, rural location, and lack of insurance were the strongest predictors for mastectomy and not receiving adjuvant radiotherapy. 22 Dragun et al examined factors influencing the receipt of mastectomy and found that determinants of higher rates of mastectomy for in situ and early stage breast cancer included stage, moderate or poorly differentiated histology, ages older than 70 years, uninsured and government-insured, rural location, receptor negative disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21–24 A cross-sectional study of women with early stage breast cancer identified factors affecting BCT versus mastectomy choice and found that age >70 years, rural location, and lack of insurance were the strongest predictors for mastectomy and not receiving adjuvant radiotherapy. 22 Dragun et al examined factors influencing the receipt of mastectomy and found that determinants of higher rates of mastectomy for in situ and early stage breast cancer included stage, moderate or poorly differentiated histology, ages older than 70 years, uninsured and government-insured, rural location, receptor negative disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Wexelman et al 21 who conducted a study of women who underwent mastectomy in the United States indicated that reconstructed women tended to be younger, have fewer chronic illnesses, more often living in urban areas and have higher incomes, as compared with those without reconstruction. Sio et al 25 also noted that young women were more likely than old women to receive aggressive therapies and have better physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Women who undergo PMBR generally live in urban areas and within zip codes with higher than average incomes . While it is known that disparities are multifactorial, investigating interaction of factors is paramount to gaining a better understanding of the obstacles to breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,7 Women who undergo PMBR generally live in urban areas and within zip codes with higher than average incomes. 8 While it is known that disparities are multifactorial, investigating interaction of factors is paramount to gaining a better understanding of the obstacles to breast reconstruction. To our knowledge, there are no existing studies that examine the interaction between geographic and racial differences in the rate of immediate reconstruction after mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The Breast Journal, Wexelman et al . from St. Luke's‐Roosevelt Hospital in New York report on disparities in immediate breast reconstruction performed based on the Nationwide Inpatient Sample data‐base from over 1000 hospitals in 42 states . This is the largest analysis of disparities in reconstruction rates among race, socioeconomic class, and geographic location to date.…”
mentioning
confidence: 99%